A comparison of justice frameworks for international research. Issue 7 (6th November 2014) - Pratt, Bridget; Loff, Bebe
Abstract : Justice frameworks have been developed for international research that provide guidance on the selection of research targets, ancillary care, research capacity strengthening, and post-trial benefits. Yet there has been limited comparison of the different frameworks. This paper examines the underlying aims and theoretical bases of three such frameworks—the fair benefits framework, the human development approach and research for health justice—and considers how their aims impact their guidance on the aforementioned four ethical issues. It shows that the frameworks' underlying objectives vary across two dimensions. First, whether they seek to prevent harmful or exploitative international research or to promote international research with health benefits for low and middle-income countries. Second, whether they address justice at the micro level or the macro level. The fair benefits framework focuses on reforming contractual elements in individual international research collaborations to ensure fairness, whereas the other two frameworks aim to connect international research with the reduction of global health inequities. The paper then highlights where there is overlap between the frameworks' requirements and where differences in the strength and content of the obligations they identify arise as a result of their varying objectives and theoretical bases. In doing so, it does not offer a critical comparison of the frameworks but rather seeks to add clarity to current debates on justice and international research by showing how they are positioned relative to one another.